The Description of Post Sectio Caesaerae Patients Pain Intensity in Tarakan Hospital Jakarta - Irianta, Ketut; Asmara, Yoseph Rohedi Yosi; Ndraha, Suzanna; Pradyanthi, I Gusti Ayu Cintya (Universitas Kristen Krida Wacana, 2022)
Numeric Rating Scale (NRS) is an efficient and easy measurement instrument used for measuring painintensity. The aim of this research is to know the description of post sectio caesaria patient pain intensityin RSUD Tarakan Jakarta. This is an observation descriptive with cross sectional aproach. 46 postsection caesaria patients were involved as the participants with totaly sampling technique. The data wascollected through NRS scale observation questionnaire in hospitalization room RSUD Tarakan fromSeptember-November. The result shows the average reduction pain scale based on the NRS 6, 12, and 24hours post sectio caesarea. It is concluded that the average reduction pain cale based on the NRS 6, 12,and 24 hours post sectio caesarea.